Vocational and Technical Education for Youth Employment: What and how should it be implemented? Lessons from Selected Secondary Schools in Dodoma Municipality - Mayega, Jovitha L. (Papers in Education and Development, 2018)
The purpose of this study was to find out what and how Vocational and Technical Education (VTE) should be implemented at secondary school for youth employment in Dodoma Municipality. To obtain data for this study, the qualitative approach using a case study was employed. The sample for the study comprised 72 respondents, of whom 18 were secondary school teachers, 40 students and 14 parents. Purposive and simple random sampling was used to select the schools and teachers, whereas the students were selected with the assistance of academic masters. Convenience sampling was used to select the parents involved in this study. Three methods were used to collect data, namely interview, focus group discussion and documentary review. The results revealed that subjects such as Sports and Games, Commerce and Book-keeping, Elementary Engineering, Additional Mathematics, Agricultural Science, Home Economics, Computing, Ceramics, Technical Drawing, Carpentry, Masonry, Plumbing, Lumbering and Music needed to be taught through VTE. When asked how VTE should be implemented, most respondents suggested the school-based approach. The study recommends the provision of modern equipment and other facilities, collaboration between the government and stakeholders in the provision of the requisite resources, and the preparation of enough VTE teachers. Key Words: Vocational and Technical Education, Employment